Lumberjanes. Parents' day - Watters, Shannon; Leyh, Kat; Sotuyo, Ayme; Ellis, Grace; Stevenson, ND (Los Angeles, CA : BOOM! Box, a division of Boom Entertainment, Inc., 2018)
Yetis, Greek gods and grootslangs are old news to the Roanoke cabin but now the Lumberjanes face their most harrowing experience yet: their parents! It's Parents' Day at camp, and with all the fun they've been having, the Lumberjanes realize that maybe their parents might not understand the things that go bump in the woods. Now the Lumberjanes must try to keep their parents away from the supernatural, even as a mysterious force tries to intervene.
Originally published in single magazine form as Lumberjanes No. 37-40--Title page verso.
Created by Shannon Watters, Grace Ellis, Noelle Stevenson & Brooke Allen--Page 5.
4.1
5-8
Keywords: Teenage girls -- Comic books, strips, etc -- Juvenile fiction; Best friends -- Comic books, strips, etc -- Juvenile fiction; Friendship -- Comic books, strips, etc -- Juvenile fiction; Camps -- Comic books, strips, etc -- Juvenile fiction; Monsters -- Comic books, strips, etc -- Juvenile fiction; Teenage girls -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Camps -- Fiction; Monsters -- Fiction; Action and adventure comics; Horror comics; Graphic novels; Comics (Graphic works)